Species of the Alpinus Group of the Genus Baetis (Ephemeroptera, Baetidae) from Ukraine - Godunko, R.J. (Вестник зоологии, 1999)
Two species from Ukraine belonging to the alpinus group of the genus Baetis are re-described. B. melanonyx (Pictet) is recorded from Ukraine for the first time (the Bystrytsya Nadvirny-anska and the Tysa river basin). The synonymy of B. alpinus (Pictet) and B. carpathicus Morton is discussed on the basis of Dziedzielewicz’s collection, from the type localities (vicinity of Khomyak Mountain, the Prut liver basin). Information on the distribution of the alpinus group species in rivers of the Ukrainian Carpathians, data on their ecology and keys to larvae and adult males are provided.